A 3D printing approach to intelligent food packaging. (September 2022) - Tracey, Chantal T.; Predeina, Aleksandra L.; Krivoshapkina, Elena F.; Kumacheva, Eugenia
Abstract: Background: Intelligent packaging and point-of-use devices designed to monitor food quality and package integrity, as well as assist in food authentication, are currently unaffordable to the food industry due to costly conventional fabrication methods, namely inkjet printing, gravure printing, and screen-printing technologies. Another major hindrance is the availability and use of safe food-friendly materials to produce the smart components ( i.e., sensors, indicators, and tags) that monitor these parameters. Recently, however, additive manufacturing (stereolithography and extrusion-based 3D printing) has emerged as a cost-effective solution for the fabrication of these smart systems from materials deemed safe and food-friendly by internationally recognised food regulation agencies. Scope and approach: This study emphasises the importance of utilizing intelligent food packaging. Regular food packaging allows potential tampering, contamination, and food fraud to go undetected. Intelligent food packaging, however, allows for real-time communication on the state of a food product and would assist in food defense and ensure consumers receive food products of the highest quality. Unfortunately, consumers are currently unwilling to shoulder the costs associated with intelligent food packaging and point-of-use devices fabricated using conventional approaches. This review explores 3D printing as a viable alternative. Key findings and conclusions: A 3D printing approach to the fabrication of intelligent packaging and point-of-use devices allows for the development of highly sensitive, self-indicating, multifunctional smart components using biocompatible nontoxic materials more cheaply than conventional fabrication methods. This would make intelligent food packaging more ubiquitous and, in turn, reduce food waste and prevent consumers from ingesting unfit food products. Graphical abstract: Image 1 Highlights: Monitoring food quality, safety, and identity. Affordable fabrication of intelligent food packaging. 3D printing utilizes nontoxic biocompatible materials that are food-safe. Sensitive multifunctional smart components\.